2005
DOI: 10.1098/rsif.2005.0030
|View full text |Cite
|
Sign up to set email alerts
|

Surface plasmon resonance shows that type IV pili are important in surface attachment by Pseudomonas aeruginosa

Abstract: Type IV pili have been shown to play a role in the early stages of bacterial biofilm formation, but not in initial bacterial attachment. Here, using the surface analytical technique, surface plasmon resonance (SPR), we follow the attachment of the bacterium Pseudomonas aeruginosa in real time. In contrast to previous studies, we show that type IV pili mutants are defective in attachment. Both mutants lacking pili (pilA), and those possessing an overabundance of pili (pilT), showed reduced SPR measured attachme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
16
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 20 publications
(37 reference statements)
2
16
0
Order By: Relevance
“…Twitching motility, mediated by pilus extension and contraction, is required for the formation of biofilms in P. aeruginosa (10, 21). Quorum-sensing (QS) system in bacteria detects cell density and regulates the expression of many genes at high cell densities.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Twitching motility, mediated by pilus extension and contraction, is required for the formation of biofilms in P. aeruginosa (10, 21). Quorum-sensing (QS) system in bacteria detects cell density and regulates the expression of many genes at high cell densities.…”
mentioning
confidence: 99%
“…Previous studies suggested that twitching motility is necessary for microcolony formation and thus essential for normal biofilm development (10, 15, 21). However, our study showed that IV pili mutant strain PAO-ΔpilHIJK formed almost the same amount of biofilm compared to the wild-type strain, PAO1.…”
mentioning
confidence: 99%
“…Different from the killing efficacy of the MB-PAA-DNP, the dispersal efficacy seemed to be about the same for both gram-positive and gram-negative bacteria, although the biofilm dispersing mechanism by MB-PAA-DNP is not yet known. One possibility might be that the singlet oxygen produced by MB-PAA-DNP would cause damage to cell membranes (lipid), pili (proteins), extracellular DNA, and other biological molecules, all of which play important roles in biofilm formation (1,5,7,12,19). These hypothetical targets warrant further studies to elucidate the dispersion mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…Recent work by Jenkins has shown that SPR is sensitive to bacterial attachment, despite the fact that bacteria are larger than the evanescent-decay length of the resonant surface plasmons. Moreover, SPR could accurately discriminate between pil mutants of Pseudomonas aeruginosa and the wild type during ear-stage attachment (16).…”
mentioning
confidence: 99%
“…Schematic representation of the SPR setup used in this study (adapted from the work of Jenkins et al[16]). P-polarized light is reflected, forming an energy wave at the gold surface.…”
mentioning
confidence: 99%